Effect Of Astaxanthin On Rat Brains Against Oxidative Stress Induced By Cadmium:Biochemical, Histopathological Evaluation - Akkoyun, Hurrem Turan; Bengü, Aydın Şükrü; Ulucan, Aykut; Akkoyun, Mahire Bayramoğlu; Ekin, Suat; Temel, Yusuf; Ciftci, Mehmet (My University, 2018)
Aim of this study is to evaluate protective impact of Astaxanthin (AST) on rats with experimentalbrain injury induced with Cadmium (Cd). 32 male Wistar albino rats were divided into four groups as Control,Cadmium, Astaxanthin (AST), Cadmium (Cd)+Astaxanthin (AST). Rat brain tissues were obtained at the endof 30th day. Malondialdehyde (MDA), glutathione (GSH) levels and superoxide dismutase (SOD) enzymeactivities were measured in brain homogenates and histopathological examination was performed. MDA levelswere improvement in cadmium administered group (p<0.01) as well as Cd+AST administered group (p<0.05)compared to control group. In addition a substantial reduction Cd+AST group was observed compared to cadmiumadministered group (p<0.01). GSH level shows a decrease in Cd and Cd+AST groups compared to control (p<0.05).SOD enzyme activity was found significantly lower in Cd and Cd+AST groups compared to control (p<0.01). Inaddition, increase of SOD in Cd+AST group compared to cadmium group was also found significant (p<0.05).Histopathological findings in the cerebral cortex and hippocampus were different between groups. In the controland AST administered groups, normal histological structure was observed in the brain, while severe lesions wereseen in the Cd administered group and in the Cd+AST group only mild degenerative lesions were observed.As a result, elevated MDA level due to Cd administration was attenuated with AST administration. Decreased GSHlevel and SOD enzyme activity due to Cd administration was increased with AST administration. In addition, ASTadministration decreased histopathological lesions. Consequently, it is thought that AST may be used for protectionagainst brain oxidative damage due to Cd.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Biyokimya ve Moleküler Biyoloji